FORECASTING OF FIRE DANGER BY WEATHER CONDITIONS IN FORESTS OF THE GREEN BELT OF KHARKIV CITY - Melnyk, Ye. Ye. (Forestry and Forest Melioration, 2018)
Introduction The methods of predicting forest fire occurrence based on the forecast by meteorological indicators are quite efficient and less costly. However, due to the nature of some forest areas, it is not always possible to precisely use the general scale and assessment of the fire danger class. Therefore, in many countries worldwide the methods are not only being actively used but also continuously refined and improved, and even local assessment scales are being developed. The aim of the study was to investigate the tendencies of the fire occurrence in the forests of Kharkiv city green belt depending on the integrated indicator of forest fire danger in different periods of fire season and to develop the local scale for fire hazard assessment. Materials and Methods The objects of research were the forests in Zhovtneve Forest Enterprise located on the territory of the green belt of Kharkiv city. The comparison of the tendencies of fire emergency for 2015–2017 with the main indicators of fire danger, based on weather conditions determined by meteorological data from the nearest meteorological station, allowed to determine the proportion of fires for various the fire danger classes during both the entire fire period and in certain seasons. These data were used to improve the assessment of the fire hazard under weather conditions for forests of the studied area. For selected seasons of a fire period, the local scales were constructed on the basis of the ratio of a certain percentage of emerging fires for various fire danger classes using the refined method of Kurbatskiy (1963). Results and Conclusions A detailed analysis of the tendencies of forest fires in the “Zhovtneve Forest Enterprise” in several decades of months has shown some similarities and features for most of the years. Such peculiarities may be related to fluctuations of precipitation and temperature during the entire fire period as well as to natural and anthropogenic specificities of the forests on the studied territory. In particular, the following factors may affect the fire hazard: a different probability of burning drier forest fuels in certain seasons, a different number of recreating people in the forest, and the need of the local population in firing the last year’s dry grass in a meadow when fire often goes over forests. The increase in the number of fires was estimated in a case of the integrated indicator of fire danger raise, which serves as a basis for determining the fire danger classes. Comparison of these data showed a reliable correlation throughout the fire hazard period. The significant differences were registered in the number of fires on average per day for the same fire danger classes when comparing the fire occurrence in different seasons. The detection of the differences as well as the revealed distribution of forest fires by fire danger classes and by seasons allowed to establish the difference between the classes throughout the fire period and to analyze in detail the features of the fire occurrence. The difference in the number of fires in different seasons of the fire period indicates that for lower fire danger classes (from I to IV), the spring season is most threatening and fire-dangerous, when the average number of fires per day is the highest and in all classes significantly exceeds the corresponding values for the summer and especially autumn periods. Particular attention should be paid to this, even for small values of the integrated indicator of forest fire danger and lower fire danger classes. In the spring, the fire danger is much higher. In the autumn, the threat of fire is decreasing even at high values of the integrated indicator of forest fire danger. Therefore, a local scale was developed, taking into account all local and seasonal peculiarities. For the studied territory and separate seasons, the data allowed clarifying the national scale. The local scale is useful for forest fire services. It helps to improve the fire forecast during a fire danger period for a certain value of the integrated indicator of forest fire danger and the fire danger class. This will serve to rationalize the work of a fire department and allow acting in accordance with the regulations of a forest fire station depending on the fire danger class under the weather conditions. 6 Figs., 3 Tables, 25 Refs.